Assessment of the Annual Effective Dose of Natural Radionuclides from Animal Bone Samples - Ahmed Abed Ibarhim; Saleh Noori Shakoor (Peerian Journals Publishing, 2025)
This study aimed to assess the annual effective dose (AED) of natural radionuclides, specifically radon gas, in animal bone samples sourced from local markets in Kirkuk, Iraq. We analyzed a total of 24 samples, encompassing bones from cows, sheep, chickens, and fish. Each sample was meticulously prepared: it was ground, and then sealed within a customdesigned exposure chamber. Radon concentrations were measured using a RAD7 detector over a 30-minute interval for each sample. The measured concentrations (in Bq/m³) were subsequently converted to Bq/kg using estimated bone density values. Based on the data, sample SHP6 exhibited the highest radon concentration at 25.1 Bq/m³ and the highest annual effective dose at approximately 4.14×10−7mSv/year. Conversely, sample SHP3 recorded the lowest values for both metrics, with a radon concentration of 4.0 Bq/m³ and an annual effective dose of roughly 0.57×10 −7 mSv/year. The AED was then calculated in(mSv/Year) unit Our results revealed exceptionally low annual effective doses, in the range of 10⁻⁷ mSv/year. These values are well below internationally accepted radiological limits. A comparative analysis with previous studies conducted in the Kirkuk region (focusing on soil and rock) indicated that animal bones exhibit significantly lower radon activity
Keywords: Radon; Annual Effective Dose; Animal Bones; Natural Radioactivity